The Effect of Integrity, Local Own-Source Revenue, and Intergovernmental Transfers on the Efficiency of Local Government Expenditure - Nafilah Shofa Azzahra; Fajar Gustiawaty Dewi (LPPPIPublishing, 2025)
This study examines the efficiency of local government expenditure in Lampung Province and analyzes the effects of integrity, local own-source revenue (PAD), and intergovernmental transfers on expenditure efficiency. Using financial data from 15 regencies and municipalities during the 2021–2024 period, the study employs Data Envelopment Analysis (DEA) with Constant Returns to Scale (CRS) and Variable Returns to Scale (VRS) approaches to measure technical and scale efficiency, followed by multiple linear regression analysis to identify determinant factors. The DEA results reveal that only North Lampung Regency achieves full efficiency, while most local governments operate below the efficiency frontier, indicating substantial potential for improvement through better input utilization and scale adjustment. Regression results indicate that integrity does not have a significant effect on expenditure efficiency, suggesting that perceptual governance indicators alone are insufficient to explain efficiency variations. Local own-source revenue (PAD) shows a significant negative effect on expenditure efficiency, implying that higher fiscal capacity may encourage expenditure expansion that is not accompanied by proportional output gains. Meanwhile, intergovernmental transfers do not significantly affect efficiency due to their mandatory nature and limited flexibility. Overall, the findings highlight that expenditure efficiency is driven more by technical and structural aspects of budget management such as planning, control, and evaluation than by revenue size alone. Strengthening fiscal discipline and managerial capacity is therefore essential to improve local government spending efficiency.